Coupling Red‐to‐blue Upconversion Organic Microcrystals with Cd0.5Zn0.5S for Efficient and Durable Photocatalytic Hydrogen Production. Issue 13 (12th May 2022) - Liu, Yanpeng; Yu, Tianjun; Zeng, Yi; Chen, Jinping; Yang, Guoqiang; Li, Yi
Abstract: For semiconductor photocatalysts with excellent performance in solar H2 production, broadening the utilization of solar irradiation is highly necessary to further improve the solar conversion efficiency. Herein, we combined a Cd0.5 Zn0.5 S photocatalyst with DPA/PdTPTBP microcrystals capable of red‐to‐blue photon upconversion, realizing substantial performance enhancement and an apparent quantum yield of 0.16% for H2 production driven by sub‐bandgap photons (600∼650 nm). Meanwhile, this system could smoothly work with H2 production rate of 1.40 mmol g −1  h −1 for as long as 40 hours under 200 mW/cm 2 irradiation with only 3% attenuation of photocatalytic activity. Moreover, the O2 ‐barrier property of DPA/PdTPTBP microcrystals assures that photocatalytic H2 production remains effective in the presence of 10% O2 by volume, which offers an opportunity for the photocatalytic application in O2 ‐enriched environments. The combination of O2 ‐resistant upconversion microcrystals and semiconductor catalysts is the most successful solution for the construction of TTA‐UC‐based photocatalytic H2 production system so far. The present study provides a clear guideline for designing new TTA‐UC‐based photocatalytic systems. Abstract : A triplet‐triplet annihilation upconversion photocatalytic H2 production system constructed by coupling Cd0.5 Zn0.5 S photocatalyst with O2 ‐resistant red‐to‐blue upconversion microcrystals (DPA/PdTPTBP) exhibit efficient and durable photocatalytic H2 production performance.